Răspunsuri

2014-06-30T12:23:51+03:00
 (x-4)(2x+7) - (3x+2)(4x+3) +(3-2x)(x+4) =
2x²-8x+7x -28 - (12x² +9x + 8x + 6) + (3x + 12 - 2x² -8x
2x²-8x +7x - 28 - 12x² - 9x - 8x -6 + 3x + 12 -2 x² - 8x
-12x² - 26 x +22
-2 ( 6x² + 13x -11)
2014-06-30T12:39:16+03:00

(x - 4)(2x + 7) - (3x + 2)(4x + 3) + (3 - 2x)(x + 4) =

= (2x^2 + 7x - 8x - 28) - (12x^2 + 9x + 8x + 6) + (3x + 12 - 2x^2 - 8x) =

= (2x^2 - x - 28) - (12x^2 + 17x + 6) + (-2x^2 - 5x + 12) = 

= 2x^2 - x - 28 - 12x^2 - 17x - 6 - 2x^2 - 5x + 12 =

=  -12x^2 - 23x - 34 + 12 =

= -12x^2 - 23x - 22

2 5 2